THE INFLUENCE OF COMPANY SIZE, LEVERAGE, AND GOOD CORPORATE GOVERNANCE ON THE COMPANY'S VALUE IN GO PUBLIC BANKING - Eni Puji Astuti; Yohanes Indrayono; Hendro Sasongko (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the influence of company size, leverage, managerial ownership, and institutional ownership on firm value in publicly listed banking companies in Indonesia. This research applies a quantitative approach using panel data regression. The study includes 20 banking firms listed on the Indonesia Stock Exchange from 2017 to 2023, generating 140 firm-year observations. The common effect model was selected based on Chow, Hausman, and Lagrange Multiplier tests. The results indicate that company size has a significant positive effect on firm value, while leverage has a significant negative effect. Managerial ownership shows no significant effect, whereas institutional ownership surprisingly demonstrates a significant negative impact. These findings challenge the conventional expectations of ownership structures enhancing firm value, suggesting potential agency issues or ineffective monitoring mechanisms. The results suggest that corporate governance practices, especially related to institutional ownership, may not always lead to enhanced firm value. Stakeholders and regulators should reassess the effectiveness of ownership structures in the banking sector and promote governance reforms tailored to local market dynamics. This research contributes to the literature by offering empirical evidence from the Indonesian banking sector, an emerging market, and by challenging the presumed benefits of institutional ownership for enhancing firm value.